Implementation of Material Requirement Planning (MRP) in Controlling Raw Materials for Shoes Products at PT.XYZ - Chandra Sukma Adhiyasa; Indra Dwi Febryanto; Prihono .; Yanatra Budi Pramana (UNIPA PRESS, 2023)
PT. XYZ is an industry in East Java that produces products made from animal skins as raw materials. The product produced by this industry is loafers. So far, this industry has had problems with leather raw materials which often experience excess supply requiring high investment, although at certain times they also experience shortages which result in not fulfilling consumer demand. MRP is a system specifically designed to ensure the availability of materials, items or components when needed to meet production schedules and ensure the availability of finished products for consumers in situations of surging demand. MRP can answer exactly what material, how much, and when (what, how much and when) is needed so that the production process can run according to schedule. The results of this study indicate that the Material Requirement Planning (MRP) method has a total raw material inventory control cost of Rp. 189,646,600 and by using the company's method, the raw material control value is Rp. 323,325,500 Savings in raw material control costs that can be obtained by applying the MRP method are Rp. 17,416,700 or about 0.94%.